2015
DOI: 10.1016/j.drugalcdep.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Double trouble: Psychiatric comorbidity and opioid addiction—All-cause and cause-specific mortality

Abstract: This study highlights the importance of assessment for PD and AUD in OUD patients in order to identify individuals at substantially elevated mortality risk to enable a more personalized approach to their medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 43 publications
12
59
1
Order By: Relevance
“…The results of this study align with the current studies which demonstrate a high prevalence of mental disorders in the OUD population (7,30,61). However, in this study, 87% of the population had a mental disorder, whereas the prevalence in the literature is approximately 50% (7,30,61). The high prevalence identi ed in our cohort may be because we examined a broad range of disorders and that our time parameter, including study time and follow-up, was much longer than in other studies (6, 7).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study align with the current studies which demonstrate a high prevalence of mental disorders in the OUD population (7,30,61). However, in this study, 87% of the population had a mental disorder, whereas the prevalence in the literature is approximately 50% (7,30,61). The high prevalence identi ed in our cohort may be because we examined a broad range of disorders and that our time parameter, including study time and follow-up, was much longer than in other studies (6, 7).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the de nition of enrollment was different from that of the previous studies because all diagnostic information from physician visits was determined using billing data from OHIP. Similar to other studies, we also found that mental disorders in the OAT population are associated with a more complex pro le of health service utilization (7,(62)(63)(64).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given that the 1991 NHIS did not include assessments of mental disorders, negative mood served as a proxy for mental health status. Among treated cohorts of people who use drugs, there is evidence that comorbid mental disorders are associated with premature mortality (Bogdanowicz et al, 2015; Nyhlén et al, 2011). Given the high prevalence of comorbidity for illegal drug use and mental disorders (Compton et al, 2007; Grant et al, 2004; Kessler et al, 2005), as well as the association of mental disorders with elevated mortality risk (Walker et al, 2015), mental disorders are a concern in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly salient as a recent study shows alcohol use disorder to be a risk factor for opioid overdose fatalities. 41 Treatment programs to prevent overdose deaths in the homeless population should be capable of broadly addressing the co-occurring use of alcohol and multiple classes of drugs.…”
Section: Discussionmentioning
confidence: 99%